2012
DOI: 10.1002/jcp.24070
|View full text |Cite
|
Sign up to set email alerts
|

Glycoxydation promotes vascular damage Via MAPK‐ERK/JNK pathways

Abstract: Oxidation and glycation enhance foam cell formation via MAPK/JNK in euglycemic and diabetic subjects. Here, we investigated the effects of glycated and oxidized LDL (glc-oxLDL) on MAPK-ERK and JNK signaling pathways using human coronary smooth muscle cells. Glc-oxLDL induced a broad cascade of MAPK/JNK-dependent signaling transduction pathways and the AP-1 complex. In glc-oxLDL treated coronary arterioles, tumor necrosis factor (TNF) α increased JNK phosphorylation, whereas protein kinase inhibitor dimethylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…or more). We observed that very low levels of p-p38 and p-JNK were detected in vascular cells, this is consistent with the previous reports [33][34][35][36]. Compared with adult control, the expression levels of p-p38 and p-JNK seem to be higher in ageing groups.…”
Section: Discussionsupporting
confidence: 92%
“…or more). We observed that very low levels of p-p38 and p-JNK were detected in vascular cells, this is consistent with the previous reports [33][34][35][36]. Compared with adult control, the expression levels of p-p38 and p-JNK seem to be higher in ageing groups.…”
Section: Discussionsupporting
confidence: 92%
“…The MAPK signaling pathway plays an important role in vascular damage. 18 Therefore, we examined the effect of H. parasuis on activation of the MAPK signaling pathway in PAVECs. The PAVECs were infected with H. parasuis , and phosphorylation of MAPK was measured using phospho-specific Abs.…”
Section: Resultsmentioning
confidence: 99%
“…MAPK1 is a component of MAP kinase family which is involved in a wide variety of cellular processes such as proliferation, differentiation, and transcription regulation and development. Many researchers have determined the MAPK signaling participate in the biological processes of vascular system such as proliferation of vascular endothelial cell [32] and vascular damage [33]. COL4A3 is a subunit of Type IV collagen and is the major structural component of basement membranes.…”
Section: Resultsmentioning
confidence: 99%